Target objects and parameters in oil electrical survey - V. S. Mogilatov (Геофизический журнал, 2012)
The resistivity is the traditional parameter for electrical prospecting. The body of a deposit is a target object in the oil electrical prospecting. Such approach dooms the petroleum electrical prospecting to a low efficiency. We need more focus on the other electromagnetic parameters and the properties of the medium, the other targets (such as halo). And this, of course, requires innovative pilot schemes in the field and alternative interpretation.